Fresno County Bar Association and American Civil Liberties Union Celebrate the Constitution at Fresno City College - Watkins, Howard::::::::: (1988)
Howard Watkins speaking at lectern; American Civil Liberties Union of Northern California representative Bill Tamayo and Ruth Gadebusch seated at panel table Table banner reads: "Celebrate the Constitution"